ACTIVITY OF ETHYL ACETATE EXTRACT FROM Chrysophyllum cainito L. LEAVES IN DECREASING BLOOD SUGAR LEVEL IN MALE WISTAR RATS - Arrijal, Imam Malikul Hadi; Ma'arif, Burhan; Suryadinata, Arief (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The high morbidity or mortality due to diabetes mellitus becomes the world health problem. That fact encourages the study about antidiabetes drugs from natural material especially plants. This study aims to analyze the effect of ethyl acetate extract from Chrysophyllum cainito L. leaves in decreasing of blood sugar level of alloxan-induced male male wistar rats. This research is considered as experimental research with pre and post test randomized controlled group design. The experimental animals in this study were 25 male male wistar rats divided into 5 treatment groups, treatment with CMC-Na (negative control), metformin with the dose of 9 mg/200gBW (positive control), and leaves extract C. cainito dose 25; 50; 75 mg/kgBW. All treatment groups had significant decrease of blood sugar levels at 7, 10 and 14 day observations with p 0.05. While in the day 3 had insignificant decrease of blood sugar level with p 0.05. Every C. cainito leaves extract doses group have the ability to decrease sugar blood level better than negative control, but still below positif control. The optimum dose in decreasing sugar blood level in this study is 75 mg/kg BW.